(3GdSQ Gdecfhfs - (3eMeO Hf eMeO GdZRGdj, CHh MGeOs
(3ChdgG (B:s
(3HYO MeO Gddg JYGdi HeG gh Cgdg hGdUdGI Ydi fHjfG hehdGfG hTajYfG eMeO Udi Gddg Ydjg hGdQVi Yf CUMGHg s
(3BNQgG (B:s
(3hef TQ GdeHZVjf CLeYjf aefYJge HU hjS hGdbQBf GdYXje hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3eUOQ GbJfGA GdCUd (B:s
(3GdeJMa GdYQGbi HHZOGO (B(268) s
(3JHUQI GdJQGLe(Bs
Keywords: (3GdJUha hGdBOGH GdTQYjIs